2014
DOI: 10.1007/s13280-014-0524-9
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment with Forced Oxygenation of the Deepwater of the Anoxic By Fjord, Western Sweden

Abstract: In a 2.5-year-long environmental engineering experiment in the By Fjord, surface water was pumped into the deepwater where the frequency of deepwater renewals increased by a factor of 10. During the experiment, the deepwater became long-term oxic, and nitrate became the dominating dissolved inorganic nitrogen component. The amount of phosphate in the water column decreased by a factor of 5 due to the increase in flushing and reduction in the leakage of phosphate from the sediments when the sediment surface bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 27 publications
5
79
0
Order By: Relevance
“…They showed that pumping 800 m 3 s −1 of winter water from 40 to 90 m with a tenfold increase in the flow due to mixing at the outlet would have prevented the development of hypoxia and anoxia that occurred during a selected period starting in early May 2003 after a complete water exchange. The characteristics of the modeled pumped flow fit well with observations made in a comprehensive, long-term pilot experiment in the By Fjord, where 2 m 3 s −1 of surface water were pumped into the usually anoxic deepwater (Stigebrandt et al, 2014b). The pumped water had a speed of 2 m s −1 through the outlet orifices.…”
Section: A Stigebrandt Et Al: Consequences Of Artificial Deepwater supporting
confidence: 68%
See 3 more Smart Citations
“…They showed that pumping 800 m 3 s −1 of winter water from 40 to 90 m with a tenfold increase in the flow due to mixing at the outlet would have prevented the development of hypoxia and anoxia that occurred during a selected period starting in early May 2003 after a complete water exchange. The characteristics of the modeled pumped flow fit well with observations made in a comprehensive, long-term pilot experiment in the By Fjord, where 2 m 3 s −1 of surface water were pumped into the usually anoxic deepwater (Stigebrandt et al, 2014b). The pumped water had a speed of 2 m s −1 through the outlet orifices.…”
Section: A Stigebrandt Et Al: Consequences Of Artificial Deepwater supporting
confidence: 68%
“…Preliminary estimates suggest a tenfold increase due to initial mixing and a further increase by a factor of 3 due to entrainment in the buoyant plume phase. Furthermore, the pumping in the By Fjord increased the rate of density reduction in the basin water by a factor of 100 and the frequency of water exchanges in the deeper parts of the basin by a factor of 10 (Stigebrandt et al, 2014b).…”
Section: A Stigebrandt Et Al: Consequences Of Artificial Deepwater mentioning
confidence: 99%
See 2 more Smart Citations
“…In deep lakes, iron is less favorable due to release mechanisms at low oxygen concentrations (see ''Quantification of P loading'' section). If ample iron is already available, artificial oxygenation can be a way to increase the redox potential and thus the binding capacity of iron (Conley 2012;Stigebrandt and Kalén 2013;Stigebrandt et al 2014;Gerling et al 2014). Bormans et al (2015) reviewed the applicability of hypolimnetic oxygenation.…”
Section: Nutrientsmentioning
confidence: 99%